Process for the production of paraformaldehyde
Patent Information
- Application Number
- CN202310433902.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-21
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-04-21
AI Technical Summary
喷雾干燥法缺点是气固分离困难,细颗粒粉尘回收难,热效率不高,设备容积大,多聚甲醛解聚难度大,作合成原料反应效果差
[0018]相比现有技术,本发明具有如下优点:
Abstract
Description
Technical Field
[0001] This invention belongs to the field of paraformaldehyde production technology, and specifically relates to a production process method for paraformaldehyde. Background Technology
[0002] In 1950, Joseph F. et al. proposed a method for producing paraformaldehyde from formaldehyde gas. This involved passing aldehyde-containing gas through a stirred paddle dryer that was drying concentrated aldehyde. The formaldehyde in the gas phase absorbed and polymerized on the surface of the solidified concentrated formaldehyde, further concentrating it to produce high-concentration paraformaldehyde. However, due to the tendency of aldehyde-containing gas to condense and solidify, leading to pipeline blockage, this method was not industrially applied. Spray granulation: Moller et al. used spray granulation or cooled and solidified concentrated formaldehyde before extrusion granulation, followed by two-stage fluidized bed temperature-controlled drying. This is one of the commercially viable processes in industrial production. Chinese patent CN200510048231.0 discloses a method for preparing paraformaldehyde using sodium hydroxide as a catalyst. CN89107085.0 describes a method for producing paraformaldehyde with a formaldehyde content of over 85% by adding a small amount of a poorly soluble, powdered alkaline earth metal compound, or a suspension dispersed in a lower alcohol, to a concentrated aqueous solution or suspension before or during cooling and curing. SFCC utilizes a patented technology from Konkan Chemical Privat, which concentrates a 45% formaldehyde solution to 75% in a stirred thin-film evaporator under a vacuum of 53-69 kPa at 85-95°C. This solution is then fed into a rotary vacuum dryer for polymerization and drying. Polymerization occurs under the action of a catalyst at 85-105°C, yielding a solid product. This solid product is then subjected to pre-crushing, sieving, and grinding processes to obtain the final paraformaldehyde product. In contrast, my country employs complex processes such as traditional intermittent vacuum evaporation concentration and spray granulation. For example, the Jilin Shijinggou Joint Chemical Plant developed a two-stage concentration, spray granulation, and two-stage drying technology to produce paraformaldehyde. The Tianjin Organic Chemical Plant's 1000 tons / year paraformaldehyde production process involves depolymerizing a 37% formaldehyde aqueous solution, vacuum concentrating it, adding a catalyst, spray granulating, and drying to obtain a 96% paraformaldehyde product. The Petrochemical Technology Development Center of Tianjin University developed a 20,000-ton / year paraformaldehyde production process, employing two-stage falling film concentration, spray granulation, and continuous drying. These processes are not only energy-intensive and costly, but also produce poor product quality, hindering large-scale production and international competitiveness, resulting in my country's long-term reliance on imports for paraformaldehyde. A better approach is to spray granulate fine-particle, water-soluble, and flowable paraformaldehyde by adding additives to 78%-85% concentrated formaldehyde and then spray granulating it under inert gas conditions at 30-40℃ in a drying chamber. To obtain high-content paraformaldehyde, a two-stage fluidized bed drying process can be used. The first stage, controlled at 45-70℃, yields paraformaldehyde with an aldehyde content of 90%-91%. The second stage, controlled at 70-100℃, further intensifies drying, achieving an aldehyde content of over 95%. Disadvantages of spray drying include difficulty in gas-solid separation, difficulty in recovering fine particulate dust, low thermal efficiency, large equipment volume, difficulty in depolymerizing paraformaldehyde, and poor reaction performance as a synthesis raw material. There is an urgent need in the art to develop a production process for paraformaldehyde to meet current application market and performance requirements. Summary of the Invention
[0003] In view of this, the present invention provides a process for producing paraformaldehyde.
[0004] A process for producing paraformaldehyde includes the following steps: using industrial formaldehyde as raw material, concentrating the industrial formaldehyde solution, adding 0.3-0.5% by mass of an additive and mixing evenly, reacting in a microwave reactor for 10-15 minutes to obtain a slurry, then mixing in 15%-20% by mass of low-polymerization degree polyoxymethylene and mixing evenly to obtain a wet material, then granulating by wet extrusion to obtain paraformaldehyde particles, and then drying by a belt dryer to obtain the paraformaldehyde granule product.
[0005] Wet extrusion granulation involves materials that have moisture content, which is sufficient to form effective particles during the extrusion granulation process. Alternatively, a solvent, such as water, can be added to the material. This solvent must be miscible with the powder material to ensure that the required effective moisture content for extrusion granulation is achieved, and to rapidly and deeply dehydrate the material to prevent high-level polymerization of formaldehyde.
[0006] The slurry material is mixed with low-polymer polyoxymethylene and mixed evenly to obtain a moist material. The granules formed by extrusion can be quickly granulated after subsequent drying.
[0007] Polyoxymethylene (POM) with low degree of polymerization and low molecular weight is prone to decomposition to produce formaldehyde. During the wet extrusion granulation process, the formaldehyde loss during drying is minimal, and the product yield is greatly improved.
[0008] After industrial formaldehyde solution is concentrated, it mainly exists in the form of OHCH2OH, with very little pure free formaldehyde. However, the decomposition of polyoxymethylene increases the content of hydrated methylene glycol, making it more prone to condensation polymerization, which increases the forward reaction rate and thus generates paraoxymethylene.
[0009] Furthermore, the wet extrusion granulation temperature is 50~52℃, the extrusion speed is 60~80rpm, and the screw sleeve diameter is 60mm. The wet material is conveyed by the screw to extrude uniform cylindrical granules with a diameter of 2.5~4mm from the die head template hole.
[0010] Belt dryers employ three to five layers of conveyor belts. Material is evenly spread onto the first layer of the belt via a feeding device, and then transferred to the next layer for continued transport. This process repeats within the drying chamber until the material falls onto the discharge device. The dryer offers stable operation, low dust levels, high capacity, and a large contact area between hot air and material, resulting in strong heat exchange and no material contamination. The material is agitated, making it suitable for drying materials prone to clumping. Throughout the drying process, the belt operates smoothly, and the material moves with the belt, maintaining a fixed relative position and uniform drying time.
[0011] Furthermore, the belt dryer has a heating temperature of 60~65℃, a discharge temperature of 30~35℃, a heating medium of water or steam, a stacking thickness of 2.5~4mm, a vacuum degree of -97~-90kPa, a conveyor belt speed of 0.1~0.15m / min, 3~5 drying layers, an effective drying section of 8~10m, and a mesh width of 1.2~2m.
[0012] Furthermore, the industrial formaldehyde concentration is achieved by pressurized distillation or vacuum cyclone separation to concentrate the industrial formaldehyde solution to a mass fraction of 60%–65%.
[0013] Furthermore, the microwave power is 400~500W and the frequency is 2450MHz.
[0014] Furthermore, the additive is hexamethylenetetramine or triethanolamine.
[0015] Furthermore, the degree of polymerization of low-degree polyoxymethylene is 100~200.
[0016] Wet extrusion granulation was previously used for the wet extrusion production of granules for chemical, fertilizer, and accelerator products. Its advantages include preventing material agglomeration, minimizing losses, facilitating metering, and making it easy to control product properties.
[0017] This invention discloses a process for producing paraformaldehyde. Formaldehyde is concentrated and then subjected to intense vibration and rotation under microwave irradiation, inducing intermolecular collisions and friction, generating heat, and rapidly raising the internal and external temperatures of the material. This achieves molecular-level stirring, uniform heating, a fast heating rate, and high reaction efficiency. Furthermore, the slurry material is mixed with low-polymerization-degree paraformaldehyde and uniformly mixed to obtain a moist material. This process not only produces high-concentration, water-soluble, and highly reactive paraformaldehyde, but also minimizes formaldehyde loss during drying, significantly increasing product yield. The product is then added to a wet granulation extruder to generate 2.5-4 mm particles. This allows drying, extrusion, and granulation to be completed in one step, producing a non-sticky, uniform, and highly flowable, soluble, and dispersible granular low-polymerization-degree paraformaldehyde product. The low-polymerization-degree paraformaldehyde, as a solid admixture, facilitates rapid and deep dehydration during the wet granulation process, preventing high formaldehyde polymerization. Simultaneously, it acts as a reactant, promoting condensation polymerization and increasing the forward reaction rate, ultimately generating paraformaldehyde.
[0018] Compared with the prior art, the present invention has the following advantages: Traditional methods for producing paraformaldehyde (PF) using spray drying and rake drying methods often result in products that are difficult to break down into lumps, have long production cycles, high energy consumption, high costs, poor product quality, limited scale, difficulties in gas-solid separation and fine dust recovery, low thermal efficiency, large equipment volumes, and slow depolymerization and dissolution of PF, leading to poor performance as a raw material for synthesis. However, in daily production practice, it has been found that microwave-reacted slurry materials can be granulated via wet extrusion to obtain PF. Furthermore, when low-solids, low-polymerization-degree PF is blended and uniformly mixed to obtain a moist material, the extrusion granulation process offers favorable conditions. The low-solids-degree PF can also increase the reaction rate, resulting in stable product quality, high automation, high production efficiency, and the ability to operate continuously for 24 hours. The drying time is short, the PF particle size is adjustable, the operation is flexible, and the PF exhibits good flowability, solubility, and dispersibility. Production costs and efficiency, as well as equipment costs and energy consumption, are significantly reduced. Implementation Example
[0019] Anhui Ruibo New Materials Co., Ltd. uses industrial formaldehyde, Jintaida uses 100% polyoxymethylene (POM), Jiangsu Fanqun Drying Equipment Factory uses DW3-1.2-8 belt dryer, Tianhua Machinery uses DL60 wet extrusion granulator, and Anxing Chemical uses hexamethylenetetramine. A production process for polyoxymethylene includes the following steps: using industrial formaldehyde as raw material, concentrating the industrial formaldehyde through pressurized distillation or vacuum cyclone separation to concentrate the industrial formaldehyde solution to a mass fraction of 60%, then adding 0.3% hexamethylenetetramine by mass and mixing evenly, using a microwave power of 400W, a frequency of 2450MHz, a stirring speed of 200rpm, and a material surface temperature of 50℃, placed in a WB-GSH microwave reactor. After reacting in the reactor for 10 minutes, a slurry is obtained. Then, 15% of low-polymerization degree polyoxymethylene (POM) is mixed into the slurry and mixed evenly to obtain a moist material. After wet extrusion granulation, POM particles are obtained. The wet extrusion granulation temperature is 50℃, the extrusion speed is 60rpm, and the screw sleeve diameter is 60mm. The moist material is extruded from the die head template hole through the screw conveyor to produce uniform cylindrical particles with a diameter of 4mm. After drying in a belt dryer, the heating temperature is 60℃, the discharge temperature is 30℃, the heating medium is water or steam, the layer thickness is 4mm, the vacuum degree is -97kPa, the conveyor belt speed is 0.1m / min, the number of drying layers is 3, the effective drying section is 8m, and the mesh width is 1.2m, thus obtaining the POM granule product.
[0020] Product: Formaldehyde content 97.5%, formic acid 0.03%, degree of polymerization 22.85, iron <0.001%, pH (90 parts water + 10 parts paraformaldehyde) 6.5, dissolution time 80℃ 80min, methanol 0.4%.
[0021] Comparative Example 1 Compared with Example 1, Comparative Example 1 omits the low-polymerization degree polyoxymethylene in the wet product material, while the remaining steps are the same.
[0022] Product: Formaldehyde content 91.3%, formic acid 0.01%, degree of polymerization 30.5, iron <0.001%, pH (90 parts water + 10 parts paraformaldehyde) 6.6, dissolution time 80℃ 150min, methanol 0.2%. Example
[0023] Anhui Ruibo New Materials Co., Ltd. uses industrial formaldehyde, Jintaida's 200-degree-of-polymerization polyoxymethylene (POM), Jiangsu Fanqun Drying Equipment Factory's DW5-2-10 belt dryer, and 99% triethanolamine from Yadong Petrochemical. A production process for POM includes the following steps: using industrial formaldehyde as raw material, concentrating the industrial formaldehyde through pressurized distillation or vacuum cyclone separation to concentrate the industrial formaldehyde solution to a mass fraction of 65%; after concentration, adding 0.5% (by mass) of triethanolamine as an additive and mixing thoroughly; using a microwave power of 500W, a frequency of 2450MHz, a material surface temperature of 50℃, and a stirring speed of 200rpm; reacting in a WB-GSH microwave reactor for 15 minutes. The resulting slurry material is then mixed with 20% low-polymerization degree polyoxymethylene (POM) by weight and mixed evenly to obtain a moist material. This material is then wet-extruded and granulated to obtain POM particles. The wet extrusion granulation temperature is 52℃, the extrusion speed is 80rpm, and the screw sleeve diameter is 60mm. The moist material is extruded from the die head template hole through the screw conveyor to produce uniform cylindrical particles with a diameter of 2.5mm. After drying in a belt dryer, the heating temperature is 65℃, the discharge temperature is 35℃, the heating medium is water or steam, the layer thickness is 2.5mm, the vacuum degree is -90kPa, the conveyor belt speed is 0.15m / min, the number of drying layers is 5, the effective drying section is 10m, and the mesh width is 2m, thus producing the POM granule product.
[0024] Product: Formaldehyde content 97.4%, formic acid 0.02%, degree of polymerization 23.42, iron <0.001%, pH (90 parts water + 10 parts paraformaldehyde) 6.6, dissolution time 80℃ 85min, methanol 0.3%.
[0025] Note: Test method: All reagents and water used in this standard are Grade III water conforming to GB / T6682. All standard solution preparations and products used in this standard are prepared according to GB / T601, GB / T602, and GB / T603. Appearance is visually inspected under natural light. Determination of formaldehyde content: Paraformaldehyde reacts with excess neutral sodium sulfite solution to produce sodium hydroxide, which is then titrated with a standard sulfuric acid solution using a potentiometric titrator. Reagents and solutions: Sodium sulfite solution: C(Na2SO3) = 126 g / L. Weigh 126 g of anhydrous sodium sulfite, dissolve it in water, and dilute to 1 L. Adjust the pH to 9.3 with 1.0 mol / L sulfuric acid, shake well, and set aside. This solution is valid for one week. Sulfuric acid standard solution: C(1 / 2H2SO4) = 1.0 mol / L. Instrument: Automatic potentiometric titrator. Analytical Procedure: Weigh 0.5g of the sample into a 100mL titration vessel using the incremental method, accurate to 0.0001g. Add 40mL of sodium sulfite solution. Titrate with standard sulfuric acid solution on a potentiometric automatic titrator to the endpoint. Read the analytical result directly from the automatic titrator. Take the arithmetic mean of two parallel determinations as the final result. The difference between two parallel determinations should not exceed 0.7%. Acidity Determination Principle: Paraformaldehyde aqueous solution depolymerizes into formaldehyde solution upon heating. Neutralize the formic acid in the sample with standard sodium hydroxide solution. Reagents and Solutions: Sodium hydroxide solution: C(NaOH) = 0.01mol / L. Potentiometric automatic titrator. Weigh 10g of the sample into a 250mL beaker, accurate to 0.0001g. Add 90mL of grade III water. Heat slowly on a stirring and heating furnace until the solution is completely dissolved. Cool to room temperature and titrate with standard sodium hydroxide solution on a potentiometric automatic titrator to the endpoint. Take the arithmetic mean of two parallel determinations as the final result. pH determination: A suspension of paraformaldehyde was prepared using grade III water. After heating to depolymerize and cooling, the pH value of the aqueous solution was measured. The procedure was as follows: 10g of paraformaldehyde sample and 90g of grade III water were added to a ground glass flask. A condenser was connected to the top of the flask. The solution was depolymerized and clarified in a 90℃ water bath, then allowed to cool to room temperature. The pH value of the solution was measured. Iron content determination was performed according to GB / T3049. 5.0g (accurate to 0.01g) of paraformaldehyde sample was weighed, added to 30mL of water, heated to dissolve, and transferred to a 100mL volumetric flask. Other steps were performed according to GB / T3049. Ash content determination: A muffle furnace (1200℃) was used. The analytical procedure was as follows: 10g of sample was carefully weighed into a dried platinum crucible (mass m1), burned at 600℃, and the residue was cooled in a desiccator and weighed (m2). Calculate the percentage content of ash X, and take the arithmetic mean of two parallel determinations as the result. Reagents and materials for methanol content determination: Nitrogen: purity ≥ 99.999% (steel cylinder); Hydrogen: purity ≥ 99.999% (steel cylinder).4.8.2 Instruments a) Gas chromatograph: equipped with a flame ionization detector (GC6890); b) Column: HP-PLOT-Q (19091P-Q04); c) Recording instrument: Agilent gas chromatograph workstation. Determination Procedure a) After starting the chromatograph, make necessary adjustments to achieve the following analytical conditions: Column temperature: 100℃ for 3 min, increase to 160℃ at 25℃ / min, hold for 2.5 min; Detection temperature: 300℃; Injector temperature: 180℃; Carrier gas nitrogen: (dried and purified by 5A molecular sieve) flow rate 1.8 mL / min; Fuel gas hydrogen: (dried and purified by 5A molecular sieve) flow rate 30 mL / min; Air: (dried and purified by 5A molecular sieve) flow rate 300 mL / min. Split ratio: 25:1; Injection volume: 1.0 μL. Qualitative analysis: Relative retention value or pure sample addition method. Quantitative analysis: Internal standard method. d) Determination: Correction factor determination: Add 25 mL of grade III water to a 50 mL ground glass conical flask, weigh 0.1 g of methanol and ethanol respectively, accurate to 0.0001 g, stopper and shake well. Turn on the gas chromatograph 6890, under the specified operating conditions, inject 0.4 μL of standard sample using a microsyringe, and collect and process the data using an Agilent workstation. Sample preparation: Weigh 25 g of paraformaldehyde, add 75 mL of distilled water, place in a round-bottom flask, heat to 80–90 °C, heat and condense until the paraformaldehyde is completely dissolved, and accurately weigh the solution mass m1. Sample determination: Weigh 40 g of the prepared formaldehyde solution and 0.1 g of ethanol using the same method, and perform other operations as above, calculate the methanol content.
Claims
1. A production process for paraformaldehyde, characterized in that, Includes the following steps: Using industrial formaldehyde as raw material, the industrial formaldehyde solution is concentrated, and then 0.3-0.5% of an additive by mass is added and mixed evenly. The mixture is then placed in a microwave reactor and reacted for 10-15 minutes to obtain a slurry. Then, 15%-20% of a low degree of polymerization polyoxymethylene (POM) with a degree of polymerization of 100-200 is mixed into the slurry and mixed evenly to obtain a wet material. After wet extrusion granulation at a temperature of 50-52°C, polyoxymethylene particles are obtained. These particles are then dried in a belt dryer under the following conditions: vacuum degree -97--90 kPa, heating temperature 60-65°C, discharge temperature 30-35°C, layer thickness 2.5-4 mm, conveyor belt speed 0.1-0.15 m / min, number of drying layers 3-5, and effective drying section 8-10 m. This yields the polyoxymethylene granule product. The additive is hexamethylenetetramine or triethanolamine.
2. The production process of paraformaldehyde according to claim 1, characterized in that, The wet extrusion granulation process has an extrusion speed of 60-80 rpm and a screw sleeve diameter of 60 mm. The screw conveyor causes the wet material to be extruded from the die head template hole to form uniform cylindrical granules with a diameter of 2.5-4 mm.
3. The production process of paraformaldehyde according to claim 1, characterized in that, The belt dryer has a heating temperature of 60~65℃ and a discharge temperature of 30~35℃. The heating medium is water or steam. The effective drying section is 8~10m and the belt width is 1.2~2m.
4. The production process of paraformaldehyde according to claim 1, characterized in that, The industrial formaldehyde concentration is achieved by pressurized distillation or vacuum cyclone separation to concentrate the industrial formaldehyde solution to a mass fraction of 60%–65%.
5. The production process of paraformaldehyde according to claim 1, characterized in that, The microwave power is 400~500W and the frequency is 2450MHz.
Citation Information
Patent Citations
Making method for polymer formol with high content of formol
CN1050201A
Process for preparing polymeric formal
CN1793097A
Binder for granulating accelerator TBBS (N-tert-butylbenzothiazole-2-sulphenamide) and method for granulating accelerator TBBS
CN102031068A
Productionmethod of alpha-polyoxymethylene
CN106832160A
Addition of amine to improve parafomaldehyde
US5898087A